2022
DOI: 10.1111/fare.12733
|View full text |Cite
|
Sign up to set email alerts
|

Exploring personal and relational motivations and processes of forgiveness in religious families

Abstract: Objective and Background We used qualitative methodology to explore forgiveness motivations and processes in an ethnically, economically, and geographically diverse sample of 198 highly religious Christian, Muslim, and Jewish families in the United States (N = 480). Prior research has identified several significant relational implications and outcomes of forgiveness. However, there is a need for additional research on forgiveness processes and motivations among highly religious families. Method Families were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Furthermore, cross-sectional work has found that prayers of confession have a positive indirect effect on psychological well-being through increasing disclosure with God, perhaps because such prayers allow more personal and intimate communication with God (Zarzycka & Krok, 2021). In prior qualitative work, participants reported that repentance might help facilitate a deeper connection with God (Clayton-Jones et al, 2016), motivate interpersonal reconciliation and forgiveness (Dollahite & Marks, 2009; Hendricks et al, 2022), act as a form of religious coping (Pietkiewicz & Bachryj, 2016), increase gratitude and positive emotions following repentance (Abernethy et al, 2016), and decrease feelings of guilt and shame (Abernethy et al, 2016; Sremac & Ganzevoort, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cross-sectional work has found that prayers of confession have a positive indirect effect on psychological well-being through increasing disclosure with God, perhaps because such prayers allow more personal and intimate communication with God (Zarzycka & Krok, 2021). In prior qualitative work, participants reported that repentance might help facilitate a deeper connection with God (Clayton-Jones et al, 2016), motivate interpersonal reconciliation and forgiveness (Dollahite & Marks, 2009; Hendricks et al, 2022), act as a form of religious coping (Pietkiewicz & Bachryj, 2016), increase gratitude and positive emotions following repentance (Abernethy et al, 2016), and decrease feelings of guilt and shame (Abernethy et al, 2016; Sremac & Ganzevoort, 2013).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Furthermore, because divine forgiveness is deeply connected to interpersonal forgiveness and self-forgiveness, it is important to understand how processes of repentance and divine forgiveness relate to these other types of forgiveness (Fincham & May, 2022). Previous research has found that seeking and receiving divine forgiveness may enable seeking and receiving interpersonal forgiveness as well as being more forgiving toward others (Hendricks et al, 2022). Relatedly, divine forgiveness has been found to moderate the relationship between self-forgiveness and individual well-being (Fincham & May, 2019).…”
mentioning
confidence: 99%
“…Following IRB approval and obtaining informed consent from participating families, semi-structured interviews regarding religion and family life were conducted by the second and third authors and their research assistants in participants’ homes from 2001 to 2016 (see Hendricks, Chelladurai, et al 2023 for additional discussion regarding the potential strengths of this expanded data collection process). Interviews included approximately 20 open-ended questions (see Appendix A), typically lasted 2 to 2.5 hours, and were audio-recorded and transcribed verbatim.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of the religious importance of repentance, contrasted with a dearth of empirical work, several social science scholars have called for research to explore the processes of repentance (e.g., Fincham and May 2023; Hendricks, Chelladurai, et al 2023). Relatedly, following a decade review of research on religion and family, Mahoney (2010) recommended that future research explore specific beliefs and practices that help or harm families rather than simply measuring general religiousness (e.g., frequency of religious attendance).…”
mentioning
confidence: 99%
“…Thus, changes in religious identity may lead to decreased consensual solidarity, operationalized as decreased religious belief similarity, which may in turn lead to decreased affectual solidarity or parent-child relationship quality. Further, shared religious devotion has been tied to positive relational outcomes, perhaps due to shared meaning and purpose as well as fostering positive relational virtues such as forgiveness (Dollahite, Marks, and Wurm 2019;Hendricks et al 2023). Thus, the lack of shared religious beliefs and ties may cause individuals to not reap the relational benefits that religion can provide.…”
Section: Intergenerational Solidarity Theory and Consensual Solidaritymentioning
confidence: 99%